IMPLEMENTASI MODEL STAD UNTUK MENINGKATKAN LITERASI BUDAYA SISWA KELAS III DI SD NEGERI 2 PLIKEN - Salma Dwi Amanda; Azis Nurrozikin; Badarudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low interest in reading written information among grade III students. This condition often causes students to experience misunderstandings or misconceptions in understanding the contents of the material, including in the context of learning about cultural diversity. The purpose of this study is to improve students' cultural literacy through the application of the Student Teams Achievement Division (STAD) learning model integrated with the Culturally Responsive Teaching (CRT) approach to the material "Different is Beautiful" in the Pancasila Education subject. This research is a Classroom Action Research (CAR) which is carried out in two cycles, each consisting of two meetings. The learning media used include happy notes in the form of traditional houses, regional dance flashcards, AR flashcards of traditional games, and diversity spinners. The results of the study showed an increase in students' cultural literacy achievements; in cycle I most students only achieved 2-3 indicators out of 6 indicators set, while in cycle II 95.2% of students achieved 4-6 indicators. Thus, the implementation of the local culture-based STAD model has proven effective in improving students' cultural literacy, both in terms of knowledge, reading skills, and attitudes of respecting diversity.